(untitled) - Ceri, Stefano (Harlow, England, 1997)
Helps you master the latest advances in modern database technology with IDEA, a state-of-the-art methodology for developing, maintaining, and applying database systems. Includes case studies and examples.
Keywords: Quản trị cơ sở dữ liệu,Database management